2016
DOI: 10.1017/s1368980016002305
|View full text |Cite
|
Sign up to set email alerts
|

Discretionary food and beverage consumption and its association with demographic characteristics, weight status, and fruit and vegetable intakes in Australian adults

Abstract: Objective: Excessive consumption of discretionary foods/beverages in the Australian population has been identified, increasing the risk of obesity and chronic disease. The present study aimed to examine the associations between demographic, anthropometric and dietary factors and the consumption of discretionary foods, discretionary beverages and discretionary foods/beverages combined. Design: Discretionary food/beverage consumption reported in two 24 h recalls was analysed, stratified by gender, age, socio-eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 38 publications
(88 reference statements)
5
50
1
Order By: Relevance
“…The degree of processing of plant foods in particular can significantly magnify the insulin response; therefore, the common prescription to source CHO from vegetables in the low‐CHO diet studies might have played an important role in regulating participants' energy intakes and improving glycaemic control. Most vegetables have a low digestible CHO content owing to their high proportions of water and fibre, and often displace the intake of highly processed CHO and discretionary foods . Many of the included low‐CHO protocols are ultimately in alignment with public health recommendations to consume a vegetable‐rich diet for chronic disease prevention and management …”
Section: Discussionmentioning
confidence: 99%
“…The degree of processing of plant foods in particular can significantly magnify the insulin response; therefore, the common prescription to source CHO from vegetables in the low‐CHO diet studies might have played an important role in regulating participants' energy intakes and improving glycaemic control. Most vegetables have a low digestible CHO content owing to their high proportions of water and fibre, and often displace the intake of highly processed CHO and discretionary foods . Many of the included low‐CHO protocols are ultimately in alignment with public health recommendations to consume a vegetable‐rich diet for chronic disease prevention and management …”
Section: Discussionmentioning
confidence: 99%
“…Dietary Guidelines internationally emphasise the selection of nutrient-dense foods whilst limiting ‘discretionary choices’, i.e., foods and beverages that are higher in saturated fat, added sugars, salt and/or empty (nutrient-poor) kilojoules [1,3,4]. In the Australian diet, discretionary choices consistently contribute over one third of daily energy intake [5,6,7], with 98.3% of Australian children and adults consuming on average 34.6% of energy intake from discretionary choices in the most recent national survey [8]. Globally, national survey data shows similar trends, with 89% of US adults consuming discretionary foods [9]; discretionary foods (i.e., non-basic foods high in saturated fats and/or added sugars) contributing 26% to population total energy intake in Mexico [10]; while foods such as hot chips, processed meat, confectionery and soft drinks [11] and sweets and cookies [12] are the highest contributors to energy intake in the UK and Brazil, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, Bayer et al (2014) found no significant association between fruit and vegetable consumption and BMI change in school-aged children. A study in Australia found that "total discretionary food/beverage consumption, defined as foods and drinks that are not necessary for a healthy diet, as well as discretionary foods and discretionary beverages independently were associated with BMI in Australian adults" (Sui et al, 2017). Thus, existing research on the association between fruits and vegetables consumption and weight status contains conflicting results.…”
Section: Discussionmentioning
confidence: 99%